"Heavy‐Atom" Donor–Acceptor Conjugated Polymers. Issue 9 (9th April 2014) - Gibson, Gregory L.; Seferos, Dwight S.
<x xml:space="preserve">Abstract</x> Heavy‐atom substitution chemistry in donor–acceptor (D–A) conjugated polymers has gained increasing attention in the past few years. Overall, the introduction of "heavy" atoms (below C in group 14; below N in group 15; below S in group 16) into D–A conjugated polymers allows control over properties through relatively straightforward synthetic chemistry, and produces materials with high molecular weights (>20 000 g mol−1), strong absorption (ε ≈ 40 000 L mol−1 cm−1), narrow highest occupied molecular orbital (HOMO)–lowest unoccupied molecular orbital (LUMO) gaps (<1 eV), as well as high charge‐carrier mobility (>10−2 cm2 V−1 s−1). This Trend article aims to describe heavy‐atom substitution effects in D–A polymers, and their applications, by systematically examining representative polymer structures. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>